Investigation of Carburetor Venturi Bore Size in Internal Combustion Engines Using Ron 95 Fuel Mixed With Bioethanol - Riswan Sepriyatno; Tri Sandi Arif Hamzah; Nur Rahmadani Jatu Matimbang; Akhmad Faruq Alhikami; Mochammad Khoirul Rosidin (Universitas Islam Raden Rahmat, Malang, 2024)
This study presents the results of an investigation into the performance and exhaust emissions of a four-stroke, 1-cylinder internal combustion engine. In order for the engine to produce optimal energy, the right fuel is needed so as to reduce exhaust emissions, which are considered very dangerous for the survival of living things. Bioethanol is considered to optimize combustion reactions in the form of CO dan HC produced, but bioethanol contains less energy compared to gasoline. The purpose of this study is to analyze the fuel v-power shell of RON 95mixed with 15% bioethanol fuel with a comparison of carburetor venturi hole sizes 26 and 28. From the results obtained, fuels with bioethanol mixtures have lower levels of waste emissions while, performance is improved compared to non-mixed petrol fuels.